Assessing Cognition in Mice. Issue 4 (2nd December 2015) - Hölter, Sabine M.; Garrett, Lillian; Einicke, Jan; Sperling, Bettina; Dirscherl, Petra; Zimprich, Annemarie; Fuchs, Helmut; Gailus‐Durner, Valerie; Hrabě de Angelis, Martin; Wurst, Wolfgang
Abstract : Genetically modified mouse models have proven useful to study learning and memory processes and the neurocircuitry and molecular mechanisms involved, as well as to develop therapies for diseases involving cognitive impairment. A variety of tests have been developed to measure cognition in mice, and here we present those established and regularly used in the German Mouse Clinic. The test paradigms have been carefully chosen according to reliability of results and disease relevance of the cognitive functions assessed. Further criteria were time efficiency and ease of application. All tests assess slightly different but also overlapping or interacting aspects of learning and memory so that they can be used to complement each other in a comprehensive assessment of cognitive function. The five protocols described are for spontaneous alternation in the Y‐maze, social discrimination, object recognition, automated assessment of learning and memory using the IntelliCage, and olfactory discrimination learning. © 2015 by John Wiley & Sons, Inc.